Structural analysis of a new carotenoid-binding protein: the C-terminal domain homolog of the OCP - Dominguez-Martin, Maria Agustina; Hammel, Michal; Gupta, Sayan; Lechno-Yossef, Sigal; Sutter, Markus; Rosenberg, Daniel J; Chen, Yan; Petzold, Christopher J; Ralston, Corie Y; Polívka, Tomáš; Kerfeld, Cheryl A (Scientific reports, 2020)
The Orange Carotenoid Protein (OCP) is a water-soluble protein that governs photoprotection in many cyanobacteria. The 35 kDa OCP is structurally and functionally modular, consisting of an N-terminal effector domain (NTD) and a C-terminal regulatory domain (CTD); a carotenoid spans the two domains. The CTD is a member of the ubiquitous Nuclear Transport Factor-2 (NTF2) superfamily (pfam02136). With the increasing availability of cyanobacterial genomes, bioinformatic analysis has revealed the existence of a new family of proteins, homologs to the CTD, the C-terminal domain-like carotenoid proteins (CCPs). Here we purify holo-CCP2 directly from cyanobacteria and establish that it natively binds canthaxanthin (CAN). We use small-angle X-ray scattering (SAXS) to characterize the structure of this carotenoprotein in two distinct oligomeric states. A single carotenoid molecule spans the two CCPs in the dimer. Our analysis with X-ray footprinting-mass spectrometry (XFMS) identifies critical residues for carotenoid binding that likely contribute to the extreme red shift (ca. 80 nm) of the absorption maximum of the carotenoid bound by the CCP2 dimer and a further 10 nm shift in the tetramer form. These data provide the first structural description of carotenoid binding by a protein consisting of only an NTF2 domain.
Keywords: bakteriální proteiny; Protein Domains; vazba proteinů; Bacterial Proteins; Cyanobacteria; krystalografie rentgenová; proteinové domény; sinice; maloúhlový rozptyl; Crystallography, X-Ray; Canthaxanthin; Scattering, Small Angle; Protein Binding; kanthaxanthin; Nucleocytoplasmic Transport Proteins; nukleocytoplazmatické transportní proteiny